2016
DOI: 10.1096/fj.201600675r
|View full text |Cite
|
Sign up to set email alerts
|

New function of the myostatin/activin type I receptor (ALK4) as a mediator of muscle atrophy and muscle regeneration

Abstract: Skeletal muscle fibrosis and impaired muscle regeneration are major contributors to muscle wasting in Duchenne muscular dystrophy (DMD). Muscle growth is negatively regulated by myostatin (MSTN) and activins. Blockage of these pathways may improve muscle quality and function in DMD. Antisense oligonucleotides (AONs) were designed specifically to block the function of ALK4, a key receptor for the MSTN/activin pathway in skeletal muscle. AON-induced exon skipping resulted in specific Alk4 down-regulation, inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Alk1 was upregulated in the gastrocnemius and diaphragm muscle of LGMD mice ( Fig 5c ). Alk4 , which was previously described as a specific myostatin type I receptor in muscles [ 21 , 22 ] was significantly increased in LGMD diaphragm muscle. Similar to Acvr2a and Acvr2b results, SGCD-null males expressed significantly higher Alk4 levels than did females.…”
Section: Resultsmentioning
confidence: 99%
“…Alk1 was upregulated in the gastrocnemius and diaphragm muscle of LGMD mice ( Fig 5c ). Alk4 , which was previously described as a specific myostatin type I receptor in muscles [ 21 , 22 ] was significantly increased in LGMD diaphragm muscle. Similar to Acvr2a and Acvr2b results, SGCD-null males expressed significantly higher Alk4 levels than did females.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, myostatin has been demonstrated to inhibit the myogenic differentiation of C2C12 cells [54,55]. ACVR1B inhibition promoted myogenetic differentiation in C2C12 in vitro, and reduced muscle mass and muscle fiber size in ACVR1B -silencing mice [18]. It is logical that miR-24-2 promotes differentiation by inhibiting ACVR1B expression to block myostatin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to participate in embryonic development, nervous system differentiation, germ cell development, tumor formation, and immunosuppression [15,16,17]. ACVR1B influences myogenesis and regulates the balance between protein synthesis and degradation by modulating the MSTN pathway to maintain muscle mass [18]. In addition, miR-210 regulates transforming growth factor-β (TGF-β)/activin signaling to promote osteoblastic differentiation by targeting ACVR1B [19].…”
Section: Introductionmentioning
confidence: 99%
“…Activin-A binds to a set of receptors (ALK4, ALK7, ActRIIA, and ActRIIB) distinct from those used by the TGF-b isoforms (Loomans and Andl, 2016). Activin-A and its receptor dimer comprising ALK4 and ACVR2A/B play a critical role in muscular development (Pasteuning-Vuhman et al, 2017), and can be produced in large amounts by dendritic cells (DCs) or following acute inflammation (Jones et al, 2004;Robson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%